Antimicrobial therapy in veterinary medicine (Blackwell Pub., 2006)
The book has four sections, focusing on pharmocokinetic - pharmacodynamic relationships of antimicrobial agents, prophylactic use of antimicrobial agents, antimicrobial chemotherapy for the neutropenic patient, prudent use of antimicrobial agents, and antimicrobial therapy in New World camelids. It includes coverage of the most recent antimicrobial agents developed for use in human or veterinary medicine